Human immunodeficiency virus type 2 infection. - Mansinho, K (1999)
The isolation of a second retrovirus, HIV-2, led to fears that a second AIDS pandemic, similar in scope and magnitude to that caused by HIV-1, might ensue. However, the peculiar biologic properties of HIV-2, namely the lower transmissibility of this virus through both sexual and vertical routes, contributed to a more regionalized distribution of the virus, which became endemic in West Africa. HIV-2 is genetically more closely related to SIV than to HIV-1. When it comes to clinical disease, the spectrum of opportunistic infections and tumors (except for Kaposi sarcoma) are similar to that observed with HIV-1. Controlled longitudinal studies suggest that the rate of progression to advanced HIV related disease and mortality are far lower for HIV-2 than for HIV-1. Understanding how, immunologically and virologically, HIV-2 behaves differently from HIV-1 may provide some insight into the mechanisms governing HIV-1 pathogenesis.